Assessment of Antioxidant Status of Oreochromis mossambicus in Fresh and Brackish Water of Thiruvarur District, Tamil Nadu from India - Priyadharsini , N.; Ravichandran, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Antioxidant biomarkers have been used to demonstrate the effects of various’ environmental stressors on certain aquatic organisms. The objective of the study is to analyze the antioxidant status of freshwater and brackish fish such as Oleochromis mosambicus in 2022. Antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase, glutathione S transferase (GST) and 、 Glutathione content (GSH) was with gills, and, Livers and muscles of fresh water fish of Oreochromis mosambicus analyzed. The results of the study showed that superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, glutathione S transferase and glutathione contained in different tissues (gills, gills and various tissues) Antioxidant enzymes such as glutathione content have been demonstrated and the liver and muscles have been reduced in Oreochromis mossambicus. The decreased activities of these enzymes may be due to contaminant exposure. This modulation in enzyme activity could be due to the mechanism by which Tilapia Oreochromis mossambicus circumvents the salinity stress caused by contaminants. The research will provide more detailed information on the response of antioxidant defenses to tilapia species in dark water environments and the mechanisms of regulation of this response. This future research will undoubtedly benefit some aspects of aquaculture and aquaculture production as well.